Intensity and timing of warming and drought differentially affect growth patterns of co-occurring Mediterranean tree species - Granda, Elena; Julio Camarero, J; Gimeno, Teresa E; Martínez-Fernández, Jesús; Valladares, Fernando (EUROPEAN JOURNAL OF FOREST RESEARCH, 2013)
Climate change involves warmer temperatures, altered precipitation patterns, increased climatic variability and, in Mediterranean regions, increased frequency and severity of droughts. Tree species may show different growth responses to these components of climatic change, which may trigger changes in forest composition and dominance. We assessed the influence of recent climatic changes on secondary growth of mature trees from four species co-occurring in a Mediterranean continental forest: Quercus ilex, Quercus faginea, Pinus nigra and Juniperus thurifera. We used dendrochronology to relate radial-growth variables \{[\}earlywood and latewood widths, basal area increment (BAI)] to annual and seasonal climatic variables for the period 1977-2007. Our results showed that Q. faginea BAI has declined, whereas J. thurifera BAI has increased over time while Q. ilex and P. nigra have maintained their growth rates. Growth was mainly favored by higher precipitations and tree size for all species. Reduced growth during extremely dry years was observed for all study species, but all of them except Q. faginea recovered their growth levels 2 years after drought. Our findings illustrate how the effects of climatic changes on growth should include analyses of seasonal climatic trends and extreme events such as severe droughts. We conclude that the seasonal timing of warming and precipitation alterations leading to drought events caused contrasting effects on growth of co-occurring Mediterranean tree species, compromising their future coexistence.
Keywords: climate change; Coexistence; Dendroecology; Drought; Mediterranean forests; Radial growth